Hubungan Terpaan Iklan, Promosi Penjualan dengan Keputusan Pembelian Produk Indihome PT.Telkom Indonesia - Cita Mahardini, Natasya; Widowati Herieningsih, Sri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
In the midst of competition ruling the internet (provider), causing companies such as Telkom Group to step business strategy development to get the target. Through advertising and sales promotion gave rise an attitude to the consumers to decide to buy the product. The purpose of this study is to determine the relationship of advertising exposure and sales promotion with the purchase decision of Indihome products. The study population is a consumer who has been hit by Indihome ads. While, the sample of research taken as many as 60 respondents with age range 19-50 years. Based on the hypothesis test conducted using Chi-Square correlation analysis, it shows the result that: Firstly, The score of signification and correlation that are has after do a test with SPSS formula: Chi-Square, is gotten the score of signification amount 0,000. While the score that shows which the cell of expected count below 5 out of 3 cell (37,5% > 20%) and the lowest expected count is 0,47. Thus, that shows the result can’t be solved. Secondly, the score of signification and correlation that are has after do a test with SPSS formula: Chi-Square, is gotten the score of signification amount 0,000. While the score that shows which the cell of expected count below 5 out of 3 cell (37,5% > 20%) and the lowest expected count is 2,10. Thus, that shows the result can’t be solved.